Factors affecting expert performance in bid evaluation: An integrated approach - Wang, Li; Ye, Kunhui; Liu, Yu; Wang, Wenjing (Frontiers in Psychology, 2022)
Experts play a crucial role in supporting decision-making in a vast majority of management practices. While recent studies have confirmed the impact of individuals’ inherent cognition and the external environment on expert performance, the mechanism between these two factors has been rarely explored. In this study, we identified 14 factors that influence expert performance in a bid evaluation and applied cross-impact matrix multiplication to examine the interdependence of these factors. The results indicate that the two dimension-related factors affect each other through a person-environment system, and poor situation perception can give rise to the deviation of expert performance. Expert performance will improve if external supervision and expertise are strengthened through deliberate practice. This study proposes a new expert performance research tool, elucidates its mechanism in bid evaluation from a cognitive psychology perspective, and provides guidelines for its improvement in workplace practice.